Realizing Bioethics' Goals in Practice: Ten Ways “Is” Can Help “Ought” - Solomon, Mildred Z. (The Hastings Center report, 2005)
A familiar criticism of bioethics charges it with being more conceptual than practical—having little application to the “real world.” In order to answer its critics and keep its feet on the ground, bioethics must utilize the social sciences more effectively. Empirical research can provide the bridge between conceiving a moral vision of a better world, and actually enacting it.